Comparative Analysis of Construction Procurement Systems Based on Transaction Costs - Rajeh, Mohammed (Auckland University of Technology, 2014)
Within construction procurement, Transaction cost economics (TCE), offers a mechanism to understand ‘unseen’ costs associated with the pre and post-contract work. Pre-contract, these include costs related to information gathering and procurement. Post-contract they include activities of contract administration and enforcement. This research investigates the relationship between procurement system and transaction costs (TCs) in the New Zealand construction industry, developing a theoretical model of relationship between procurement systems and TC. The model was operationalized and developed into a questionnaire. A cross-sectional sample approach was deployed, involving questionnaire survey, interviews, and research verification through ‘real world’ cases. Data was sought from professionals in management, design and operations (i.e. project managers, architects, engineers, quantity surveyors, and procurement officers). These professionals represented several construction organizations and NZ Councils (Auckland, Hamilton, Wellington, Christchurch, Dunedin). TCs were measured using time-spent conducting procurement related activities as a surrogate for cost. Professionals evaluated their time spent on procurement activities using a 5-point Likert scale, comparing the Traditional and Design-Build delivery systems. 96 responses (74 usable) were received from a sampled population of 360 (27% response). This data was triangulated with interviews to test and explain the model. The tests included Validity and Reliability Tests, Path Analysis, Regression Analysis, Factor Analysis, and Structural Equation Modeling (SEM). The primary analytical technique used was Structural Equation Modelling to yield information on Goodness-of-Fit, model development and comparison, and confirmatory strategies. SPSS Amos 21 statistical software was used for data analysis and model development. The data demonstrated univariate and multivariate normality assumptions underlying SEM testing of research hypotheses. Of 43 hypotheses tested, six null hypotheses were rejected, demonstrating a positive relationship between the costs of information, procurement, administration, and enforcement with TCs. Additionally environmental uncertainties have indirect significant impact on TCs. The results suggest procurement systems have indirect impact on TCs, which is fully mediated by costs of information, procurement, administration, and enforcement. Finally, for research results verification, the models were applied to real-life cases (four Traditional, two Design-Build). TCs were calculated using regression equations based on factor loadings in the Traditional and Design-Build models. It was found that TCs in the Traditional system amounts to 18.5% of the annual salary cost of a project manager (as an indicator quantum), while in the Design-Build system, it amounts to 14.5% of the annual salary cost of a project manager. This study applies a new theoretical model for procurement selection based on TCs, investigating and empirically demonstrating the influence of procurement system on TCs in construction. It also offers a new plausible explanation for the factors influencing TCs in procurement. The findings have practical implications on construction business practice due to their robust empirical nature and theoretical framework, which might enhance the performance of the construction industry. The study contributes to the procurement selection in construction, by introducing a new conceptual model for the link between procurement systems and TCs. It has extended the current practices for procurement selection by estimating TCs for different procurement systems, specifically for the Traditional and Design-Build systems for comparison. This study emphasizes ‘in-house’ TCs from the perspective of the client, consequently the study recommends that the work be expanded to determine the ‘out-of-house’ TCs from the contractor perspective. Furthermore that to expand the relevance of the findings further work using the same methodology should be used to measure TCs for other procurement systems for comparison purposes. Finally, this study calculates TCs within projects, so it was recommended to further explore intra-organizational TCs in construction.
Keywords: Comparative; Construction; Procurement systems; Transaction costs